HIV status disclosure rate and reasons for non-disclosure among infected children and adolescents in Enugu, southeast Nigeria - A.C. Ubesie; K.K. Iloh; I.J. Emodi; N.S. Ibeziako; I.N. Obumneme-Anyim; O.N. Iloh; A.C. Ayuk; C.J. Anikene; J.E. Enemuo (Taylor & Francis Group, 2016)
Aims: To determine the rate of HIV status disclosure, caregivers' reasons for non-disclosure, and factors influencing disclosure among a sample of HIV-infected children in Enugu, southeast Nigeria. Methods: Data were collected prospectively via a questionnaire on HIV-infected children and their caregivers who visited the pediatric HIV clinic of the University of Nigeria Teaching Hospital between July 1, 2012, and June 30, 2013. The data analysis was performed using Statistical Package for the Social Sciences version 19 software. Results: Caregivers of 107 children (age 5-16 years; mean 10.1 ± 3.2 years) were enrolled in the study. There were 53 (49.5%) boys and 54 (50.5%) girls. HIV status had been disclosed to 31 (29%) of them. The major reason for non-disclosure was the child being considered too young. Age (p < .001), age at HIV diagnosis (p < .001) and baseline CD4 count (p = .008) were seen as significant predictors of HIV disclosure. Conclusions: There is a low rate of HIV disclosure to infected children, and it was found to be lower for younger children. We recommend improving efforts for disclosure counseling to caregivers in pediatric HIV clinics.